Research on the Impact of Digital Inclusive Finance on the Urban-Rural Income Gap ——Panel Analysis Based on Province-Level Data in China - Gu, Miaoxi (Asia Pacific Economic and Management Review, 2025)
With the rise of digital technology, digital inclusive finance has emerged as a game-changing innovation in modern finance. It’s been instrumental in making financial services more accessible and convenient, reshaping income distribution patterns and fueling economic growth. This paper delves into the urban-rural income disparity stemming from financial exclusion, examining the impact of digital inclusive finance on this gap. Using panel data from 31 provinces and the latest Peking University digital financial inclusion index, we conducted empirical analyses to explore the overall and threshold effects. Our findings clearly indicate that the expansion of digital inclusive finance in China is significantly bridging the urban-rural income gap. Furthermore, our research reveals that the convergence effect of digital inclusive finance on the urban-rural income gap is contingent on thresholds related to economic development and urbanization. Finally, we propose actionable policy recommendations to foster the robust development of digital inclusive finance and promote urban-rural integration.